Globalización neoliberal y crisis de la educación - Márquez Montoya, Johanna (Educación, 2017)
This work is part of the research, neoliberal globalization and crisis in education. From a critical perspective, is intended to show that one of the education crisis, is primarily by the influence of neoliberal globalization, which has led to a modification in the anthropological image of man. The current view has affected the process of formation of the subject; therefore it is necessary to find the answer to the question for the man. In addition, the task of school spaces is mediated by the influences of capitalism; it should form and transform the human, to respond to the modifications of the time. Shows how under the modern coordinates make a new conception of human, causing a rupture in the anthropological image of man.